Fire Resistance of Axially Loaded Slender Concrete Filled Steel Tubular Columns - Leite, G. S.; Gomide, K. A.; Moreno, A. L.; Silva, V. P. [UNESP]; Kodur, V; Franssen, J. M. (Destech Publications, Inc, 2010)
The concrete filled steel tube (CFST) column is a composite member that consists of a steel tube filled with concrete. Concrete inside the steel tube enhances the stability of the steel tube, and the steel tube in turn provides effective lateral confinement to the concrete. Compared to conventional thin walled steel tube columns or reinforced concrete columns, the CFST column thus has the advantages of high load-carrying capacity, inherent ductility and toughness. Small diameters for these CFST columns, outside the range of design Codes validity, have been used. In this paper are presented the results obtained in the experimental research of concrete filled steel tube (CFST) columns of 114.3 mm and 168.3 mm in diameter, subjected to loading levels corresponding to 30%, 50% and 70% of the ultimate loading at ambient temperature, tilled with the usual concrete strength (25 MPa) and high compressive strength (75 MPa). The experimentally discovered effects of these parameters are discussed and the validity of Eurocode procedures for FCST columns with small diameters has been established by comparing the experimental results and analytical results.